IDENTIFICATION OF FISHING POTENTIAL FOR LOBSTER IN ACEH JAYA SEA WATERS - Hafinuddin Hafinuddin; Iyan Al Misbah; Samsul Bahri; Heriansyah Heriansyah (Universitas Mataram, 2024)
The waters of Aceh Jaya Regency are included in the 572 fisheries management area (WPP) which is located on the west coast of Sumatra which has the potential for lobster fisheries. However, there is limited information about the biological condition of the lobsters caught, the composition of their length and weight, and even limited data and information about potential fishing areas for lobster fishing in Aceh Jaya Regency, so this study aims to identify fishing areas where lobsters are often caught and identify the types of lobsters caught. caught lobsters. The research was carried out at PPI Rigaih in the East Season from April to May 2022. The research method was carried out by experimental fishing with data collection techniques consisting of interviews and observation. The results showed that the lobster catches obtained during the research were sand lobsters (panulirus homarus) by 50%, bamboo lobsters (panulirus longipes) by 45% and batik lobsters (panulirus longipes) by 5%. The fishing area has been identified at 04°37'45.99